Evaluating IT Performance Management in the Faculty of Industrial Engineering at Telkom University Through COBIT 2019 Domain MEA01 in Alignment with LAM-INFOKOM Standards - Vega Putra Pradana; Muharman Lubis; Lukman Abdurrahman; Raied Ali Alqahtani; Ikhlas Fuad Zamzami; Rafian Ramadhani (Electronic Integrated Computer Algorithm Journal, 2024)
This study examines the application of the COBIT 2019 framework within the Faculty of Industrial Engineering at Telkom University, specifically focusing on the Monitor, Evaluate, and Assess (MEA) domain to assess IT management performance against the standards set by the Independent Accreditation Body for Informatics and Computer Science (LAM-INFOKOM). Through a meticulous analysis, a significant gap was identified in MEA01.04 - Analyze and Report Performance, indicating a lack of proper documentation for change recommendations in objectives and metrics. Recommendations to bridge this gap include the incorporation of a Research Analyst role, clarification of responsibilities, provision of data analysis training, enhancement of inter-team communication, establishment of clear policy guidelines, and the creation of specialized record formats. These suggestions aim at improving the alignment of IT governance with both COBIT and LAM-INFOKOM standards, enhancing IT performance management, and ensuring a strategic fit between IT operations and organizational goals. The findings underscore the critical role of structured IT governance in achieving operational excellence and sustaining competitive advantage in the digital era.